Analysis Of Islamic Marketing Strategies In Increasing Muslim Costumer Confidence In Halal Products: ISLAMIC MARKETING - Qonita, Fika; Rizqina, Nala Rosida; navilatul maula, ahla; Asytuti, Rinda (UIN Mataram, 2024)
The halal product market is growing rapidly along with the increasing number of Muslim consumers in the world. This opens up opportunities for businesses to market their products using Islamic marketing strategies. Therefore, this analysis aims to discuss effective Islamic marketing strategies in increasing Muslim consumer confidence in halal products, as well as discussing the challenges and opportunities associated with a sustainable halal market. The research method used in this research is library research, which is a series of studies related to library data collection methods, or research whose research objects are explored through a variety of library information by collecting data from various sources such as scientific journals, articles, and books. The results showed that there are several Islamic marketing strategies that are effective in increasing Muslim consumer confidence in halal products, namely: Principles, Practices, and Characteristics of Marketing, Objectives and Functions of Islamic Marketing, Muslim Consumer Behavior Trust, Factors Affecting Muslim Consumer Trust, Halal Products. With that, the application of effective Islamic marketing strategies can increase Muslim consumer confidence in halal products, so as to increase sales and market share of halal products.